Industrial training report: Petroliam Nasional Berhad (PETRONAS) / Anis Nazifah Asmady Fatiman - Asmady Fatiman, Anis Nazifah (Universiti Teknologi MARA, Perlis, 2024)
In the realm of Organisational Development and Design (ODD), Petroliam Nasional Berhad (PETRONAS) offered a stimulating internship experience. Experiencing ODD in action, contributing to ongoing projects, and comprehending the function of ODD in a multinational oil company such as PETRONAS were the main goals of the internship. Using a variety of techniques and procedures, such as Microsoft Outlook, Microsoft Excel, and MyCareerX, the internship delivered significant findings and understandings crucial to the field of ODD. Using Microsoft software efficiently, corporate communication and presentations, and email interaction in a professional manner were among them. Plenty of valuable lessons were learned throughout the internship, especially in areas like handling data, developing a business case, position benchmarking, and change management. Unavoidably, difficulties arose. These included the intricate organizational structure of PETRONAS, a tight deadline, and a high level of communication with the Account Management (AM). Nevertheless, each difficulty offered a chance for development and learning, leading to creative problem-solving and flexible approaches. To sum up, the internship at PETRONAS in the ODD department was a priceless opportunity to become entirely involved in practical ODD duties, leading to important discoveries, lessons learned, and practical suggestions. The experience cultivated a stronger awareness of the role of ODD in determining the future of a worldwide energy company such as PETRONAS, in addition to improving practical skills.